Influence of Microfin Tube on Heat Transfer during Flow Boiling of R134a Refrigerant - Vidhyarthi, Neeraj Kumar; Deb, Sandipan; Gajghate, Sameer Sheshrao; Cardoso, Elaine Maria [UNESP]; Das, Mantu; Pal, Sagnik; Das, Ajoy Kumar (Wiley, 2024)
This research looks into the domination of flow boiling on the efficiency and sustainability of refrigeration and air conditioning systems. Specifically, it focuses on the characteristics related with heat transfer of refrigerant R134a within both smooth and microfin tubes, each having 9.52 mm outer diameter. The features of microfin tube have distinct configuration with a 46° apex angle and a 22° helix angle, resulting in a surface area 1.62 times greater in comparison to smooth tube. Through a comprehensive experimental analysis, the study examines the influence of key parameters (mass flux; saturation temperature; heat flux; and average vapor quality) on heat transfer coefficients (HTCs). Notably, the HTC exhibits significant enhancements at mass flux of G = 125 kg m2·s1, encountering challenges related to dry-out at elevated vapor quality levels. The results reveal that microfin tubes consistently outperform smooth tubes, exhibiting heat transfer coefficients up to 270% higher across various operational conditions. Furthermore, the experimental data are rigorously validated through computation analysis with authentic flow boiling heat transfer models, demonstrating strong agreement.